OP82 Systematic review of digital interventions to improve the diet and physical activity behaviours of adolescents. (2nd September 2017) - Rose, T; Barker, M; Jacob, CM; Lawrence, W; Strommer, S; Vogel, C; Woods-Townsend, K; Inskip, H; Baird, J
Abstract : Background: Adolescents have poor diets and insufficient physical activity (PA) levels, which can lead to non-communicable diseases in later life. Adolescence is a key stage for establishment of lifelong health behaviours. Digital platforms offer inexpensive means of delivering health interventions to large numbers of adolescents, but little is known about their effectiveness in supporting sustained changes. This systematic review was conducted to synthesise evidence on the effectiveness of digital interventions to improve diet quality and increase PA in adolescents, to identify effective intervention components and to assess the cost-effectiveness of these interventions. Methods: A systematic review of digital interventions to improve the diet and/or physical activity behaviours of adolescents was carried out according to established guidance. A search of MEDLINE, PsycINFO, CINAHL, PubMed Central, Embase, ERIC, the NHS EED and CENTRAL was conducted using a combination of MeSH and free text terms. Abstracts were assessed by two independent researchers against review inclusion criteria (intervention studies with and without a control group, participants aged 10–19, interventions that included a digital component, studies that measured a diet or PA outcome at baseline and follow-up, any setting and any population of adolescents). For included studies, data extraction and quality assessment were performed using a form designed to capture key information to answer the research questions. We then analysed data to identify key intervention features that were associated with significant improvements in behaviour. We also aimed to collect data on cost-effectiveness of included interventions. Results: The search returned 6792 results, of which 86 full texts were selected for screening. After assessing these against eligibility criteria, 27 intervention studies were included in the review. Most (n=15) were website interventions. Other delivery methods were text messages (n=4), gamified interventions (n=3), multi-component interventions that included a digital element (n=3), email (n=1), and social media (n=1). Significant behaviour change was often seen when interventions included diet and physical activity education, goal-setting in conjunction with self-monitoring, and parental involvement. None of the included publications reported cost-effectiveness. Due to heterogeneity of studies, meta-analysis was not feasible. Conclusion: It is possible to effect significant health behaviour change in adolescents through targeted digital interventions that incorporate education, goal-setting, self-monitoring and parental involvement. Most of the evidence relates to websites and further research is needed to assess effectiveness of interventions delivered via alternate media such as smartphone apps. Longer term outcomes should be evaluated. Future trials of digital interventions need to evaluate cost-effectiveness.